2000
DOI: 10.1116/1.591328
|View full text |Cite
|
Sign up to set email alerts
|

Aligned carbon nanotube films for cold cathode applications

Abstract: Thin film material of oriented multiwall carbon nanotubes was obtained by noncatalytical chemical vapor deposition in a glow-discharge plasma. The film phase composition, surface morphology, and structural features were studied by Raman and electron microscopy techniques. Low-voltage electron field emission of thin film nanotube material was obtained and examined in diode configuration. The I-V curves in Fowler-Nordheim coordinates were linear and the corresponding threshold average field was about 1.5 V/m. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…For example, surfactants have been used to template the synthesis of MCM-41, [5] or other porous silicates [6,7] and oxides. [8] The use of microporous zeolites such as Y, ZSM-5, mordenite, L and more recently beta (BEA) as templates, [9,10] has been investigated to produce carbon materials with a controlled microporosity. Moreover, zeolites, such as Y, ZSM-5, BEA, used as supports of transition metal catalyst, [11±14] permit to produce carbon nanotubes by catalytic decomposition of different hydrocarbons.…”
Section: Characterization Of Nanocarbons Produced By Cvd Of Ethylene mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, surfactants have been used to template the synthesis of MCM-41, [5] or other porous silicates [6,7] and oxides. [8] The use of microporous zeolites such as Y, ZSM-5, mordenite, L and more recently beta (BEA) as templates, [9,10] has been investigated to produce carbon materials with a controlled microporosity. Moreover, zeolites, such as Y, ZSM-5, BEA, used as supports of transition metal catalyst, [11±14] permit to produce carbon nanotubes by catalytic decomposition of different hydrocarbons.…”
Section: Characterization Of Nanocarbons Produced By Cvd Of Ethylene mentioning
confidence: 99%
“…[3] Nanomanipulation techniques have been used for fabricating single-nanotube devices, such as sensors and field effect transistors, [4±6] but the probability of selecting the proper nanotubes needed for device function is low and these techniques are generally much too inefficient and unreliable to be used for making commercial practice. Nevertheless, strategies have been developed and practiced in the laboratory for fabricating carbon nanotube forests and other oriented nanotube assemblies (which can be used for field emitting devices), [7,8] self-standing carbon nanotube films (the so-called ªbucky-papersº), [9,10] and polymer and ceramic composites. [2,11±15] The addition of carbon nanotubes to polymeric or epoxy matrices results in composites with enhanced mechanical properties and electronic transport.…”
mentioning
confidence: 99%
“…Wherever the catalyst nanoparticles are found in growth experiments, i.e., on the NT tips or on the substrate, the majority of experimental reports refer to a model of carbon filament growth by continuous C diffusion or extrusion through the metal nanoparticle 29-31 ͑''tip'' or ''base'' growth model͒. However, NT forests have also successfully been grown by plasma enhanced CVD even without a catalyst, 28 suggesting that another kinetical mechanism may be involved in this process. Additionally, in our recent communication 32 we have provided an order to magnitude analysis of CVD process of carbon NT forest growth outlining several contradictions which arise in the application of the model [29][30][31] for a particular experimental study where the Fe catalyst remained at the bottom.…”
Section: Introductionmentioning
confidence: 98%
“…The high-resolution transmission electron microscopy micrograph of NCNTs showed that nanonodes usually have high curvature surfaces. Obraztsov et al 7,8 have proposed a CNT field emission model in which carbon atoms tend to have bonds similar to sp 3 other than the normal sp 2 of graphite. In the graphite lattice, carbon atoms are bonded in planar layers with sp 2 bonds.…”
Section: Field Emission Of Nodular Carbon Nanotubesmentioning
confidence: 99%